Six-Year Evaluation of Motiva Round and Ergonomix SmoothSilk Surface Silicone Breast Implants: A Two-Center, Two-Surgeon Outcome Analysis of 1053 Primary and Secondary Breast Augmentations and Augmentation Mastopexy. (9th November 2022) - Randquist, Charles; Jaeger, Marie; Stavrou, Demetris
Abstract: Background: The emerging concerns around breast implant-associated anaplastic large cell lymphoma and other chronic inflammatory-related conditions have instigated a wider use of smooth devices. Objectives: The authors aimed to present 6-year data following the introduction of Motiva implants (Establishment Labs Holdings Inc.; Alajuela, Costa Rica) into their previously texture-dominated practice. Additionally, the authors aimed to provide technical recommendations on how to efficiently incorporate these devices into surgical practice and minimize the learning curve. Methods: Data of 1053 primary and secondary breast augmentations conducted between April 2015 and December 2020 in 2 centers (Victoriakliniken in Sweden and the European Institute of Plastic Surgery in Cyprus) were retrospectively evaluated to obtain data on chosen implant characteristics and complications that led to reoperation, prior to and following modifications to surgical practice in 2018. Results: The data from 6 consecutive years demonstrate a low device-related complication rate with Motiva implants. In 2018, following adaptions in surgical practice, the complication rate significantly declined. Conclusions: Motiva implants demonstrate a low complication rate and safety profile for women undergoing primary and secondary breast augmentation procedures. However, to reap the benefits of the antifibrotic profile, technical adaptions and optimal patient planning based on the patient and device characteristics are instrumental. Employing the key principles laid out in this study provides a means for delivering both clinically safe options to patients with aesthetically pleasing long-term results. Level of Evidence: 4: